Effect of load models in distributed generation planning - Singh D.; Misra R.K.; Singh D. (My University, 2025)
The effect of load models on distributed generation (DG) planning in distribution system is investigated in this work. It is shown that load models can significantly affect the DG planning. Normally a constant power (real and reactive) load model is assumed in most of the studies. Such assumptions may lead to inconsistent and misleading results about deferral values, loss reduction, payback period, and other subsequent calculations. It has been demonstrated that DG planning based on such assumptions would not be effective after implementation. It is shown that load models can significantly affect the optimal location and sizing of DG resources in distribution systems. A comparative study of real and reactive power loss, real and reactive power intake at the main substation and MVA support provided by installing DG resources for different type of loads models has been performed. © 2007 IEEE.